Asset allocation considerations for pension insurance funds : Theoretical analysis and empirical evidence - Hertrich, Christian (Springer Fachmedien Wiesbaden, 2013)
Pension Insurance Funds are the largest external occupational pension plan in Germany. Occupational pension schemes are expected to play a more relevant role in the future as a substitute for the statutory pension system. Christian Hertrich analyses in this context the suitability of Social Responsible Investments (SRI) as well as Alternative Investments for the strategic asset allocation of Pension Insurance Funds within the prevailing regulation as well as supervisory framework in Germany. The author completes his empirical analysis by simulating alternative investment models that do not adhere to existing regulation. Using advanced econometric models and simulation techniques, the author is able to replicate different asset allocation strategies that in combination with the calculation of adequate risk-return parameters offer valuable conclusions for researchers and practitioners.   Contents ·         Pension Insurance Funds ·         SRI ·         Alternative Investments ·         Econometrics ·         Asset Allocation Models   Target Groups ·         Researchers and students in the field of Portfolio Management, Financial Econometrics, SRI, Alternative Investments, Occupational Pension Systems ·         Practitioners involved in the asset allocation of pension funds   About the Author Dr. Christian Hertrich obtained his doctorate degree at the Department of Corporate Finance of the University of Stuttgart (Germany).